Country Assessment on Youth Violence, Policy and Programmes in South Africa - World Bank (Washington, DC, 2017)
It is increasingly recognized that young people are central to issues of crime and violence in South Africa. While research, policy and programming have historically focused on children and adults, there is a growing emphasis on youth as both victims and perpetrators of violence. This report presents the findings of a country assessment commissioned by the World Bank to support its incorporating human rights into youth violence programming and policy dialogues in Mexico and South Africa project. This aims to encourage policy dialogue on youth and violence with the South African government and other stakeholders. The report: (i) examines the current situation of youth violence in South Africa; (ii) summarizes the policy response by the government and the prevailing legal and institutional framework; (iii) identifies innovative programming by civil society organisations; and (iv) identifies entry points for deeper policy dialogue and improved interventions to address youth violence.